A guideline for using web-based AHP system - Ayu, Media Anugerah; Al-Azab, Mohammed Fadwa Gamal (IIUM Press, 2011)

(untitled)
This chapter discusses the guidelines and step by step procedures in using the web-based multi criteria decision making using Analytical Hierarchical Process (AHP) method, which is presented in the previous chapter. Readers will be guided carefully starting from the development of the decision process towards the final decision itself, based on the criteria and choices supplied to the system. It is hoped that from this chapter, readers will be able to learn and understand the process flow of multi criteria decision making using Analytical Hierarchical Process and also be able to use the system without much difficulties, lnsha Allah